Pengaruh Konsentrasi Yeast Saccharomyces Cerevisiae Dan Waktu Fermentasi Terhadap Pembentukan Bioetanol Dari Mikroalga Chlorella sp. - Dewi Kusuma Nurmalasari; Sri Rezeki Muria; Chairul Chairul (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Bioethanol is an alcohol produced from the fermentation process. Bioethanol is also called ethyl alcohol, which is produced through a microbial process, which is the opposite of ethanol synthesized from petrochemical sources. Microalgae Chlorella sp. can be used as raw material for bioethanol by utilizing microorganisms. Microorganisms used to process microalgae Chlorella sp. to become bioethanol is Saccharomyces cerevisiae. The purpose of this study was to determine the effect of Saccharomyces cerevisiae yeast concentration on bioethanol formation and determine the effect of fermentation time on bioethanol formation. This research phase consisted of hydrolysis, inoculum making, bioethanol fermentation, separation and analysis of bioethanol concentration. The variation of bioethanol fermentation time is 1, 2, 3, 4 and 5 days, while the variation of Saccharomyces cerevisiae concentration is 0.2%; 0.4%; 0.6% and 0.8% (w/v). The optimum fermentation results is bioethanol 2% (v/v) or 15.876 g/L. This optimum bioethanol concentration was obtained on the 5th day of bioethanol fermentation with a yeast Saccharomyces cerevisiae concentration of 0.6% (w/v). Keywords: bioethanol, fermentation, microalgae, yeast saccharomyces cerevisiae